Pore-forming protein complexes from Pleurotus mushrooms kill western corn rootworm and Colorado potato beetle through targeting membrane ceramide phosphoethanolamine - Panevska, Anastasija (Sci Rep, 2019)
Aegerolysins ostreolysin A (OlyA) and pleurotolysin A (PlyA), and pleurotolysin B (PlyB) with the membrane-attack-complex/perforin domain are proteins from the mushroom genus Pleurotus. Upon binding to sphingomyelin/cholesterol-enriched membranes, OlyA and PlyA can recruit PlyB to form multimeric bi-component transmembrane pores. Recently, Pleurotus aegerolysins OlyA, PlyA2 and erylysin A (EryA) were demonstrated to preferentially bind to artificial lipid membranes containing 50 mol% ceramide phosphoethanolamine (CPE), the main sphingolipid in invertebrate cell membranes. In this study, we demonstrate that OlyA6, PlyA2 and EryA bind to insect cells and to artificial lipid membranes with physiologically relevant CPE concentrations. Moreover, these aegerolysins permeabilize these membranes when combined with PlyB. These aegerolysin/PlyB complexes show selective toxicity toward western corn rootworm larvae and adults and Colorado potato beetle larvae. These data strongly suggest that these aegerolysin/PlyB complexes recognize CPE as their receptor molecule in the insect midgut. This mode of binding is different from those described for similar aegerolysin-based bacterial complexes, or other Bacillus thuringiensis Cry toxins, which have protein receptors. Targeting of Pleurotus aegerolysins to CPE and formation of transmembrane pores in concert with PlyB suggest the use of aegerolysin/PlyB complexes as novel biopesticides for the control of western corn rootworm and Colorado potato beetle.